A comprehensive synthesis of differentiated instruction approaches in mathematics - Bahurudin Setambah, Mohd Afifi; Mat Saad, Muhammad Ikhwan; Che Md Ghazali, Nor Hasnida binti; Adnan, Mazlini (LUMAT: International Journal on Math, Science and Technology Education, 2025)
This study endeavors to provide a comprehensive synthesis of theoretical frameworks in educational research, with a specific focus on investigating and comparing differentiated instruction (DI) approaches across diverse dimensions. This study aims to address the challenge of meeting diverse student learning needs in mathematics by synthesizing various differentiated instruction approaches to provide a clearer framework for educators. Employing a systematic literature review methodology, the research utilized the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) technique from 2013 to 2023. The search for relevant articles over the past ten years was conducted across prominent databases, including ERIC, Scopus, and Google Scholar. A rigorous screening process identified 3220 articles, from which 17 were selected for in-depth analysis, following the PRISMA-P flow chart process as a guide. This study synthesizes research on differentiated instruction in mathematics, highlighting various aspects such as process, product, content, and learning environment. The majority of researchers focus on the process of differentiation, examining how teaching methods are adapted to suit diverse student needs. Meanwhile, fewer studies explore the learning environment's role. The implications of this study suggest that educators should prioritize adapting teaching methods (process differentiation) to address diverse student needs, as this is where most research is focused.